Предмет: Математика,
автор: leonidpetrovich
Решииие срочно, срочно помогите 24 б дам
Приложения:
![](https://files.topotvet.com/i/dba/dbad1e1dab4640314747f75a1a5c3604.jpg)
![](https://files.topotvet.com/i/ecf/ecf3057306c1840b8fc33c43b2e2afca.jpg)
![](https://files.topotvet.com/i/8b4/8b4aaf464fdc763c4c20236156c98d49.jpg)
Ответы
Автор ответа:
0
8х^2-4x-x^2+9=7x^2-4x+9
p^2-11p+3p-33+p^2+12p+36=2p^2+4p+3
7a^2+14ab+7b^2=7a^2+7b^2
y(y^2-49)=y(y-7)(y+7)
-3(a^2+2ab+b^2)=-3(a+b)
c^2-d^2-c+d=(c-d)(c+d)-(c-d)=(c-d)(c+d-1)
(a-1)(a+1)(a-1)+1)=(a^2-1)*a=(9-1)(-3)=-24
((у-6)-3у)(у-6)+3у)=(-2у-6)(4у-6)
(а-4)(1-4а+4а^2)=(а-4)(1-2а)^2
x-[^2-10x-25=12-5x-30-x^2-6x
-9x-x^2-25=-x^2-11x-18
-9x+11x=-18+25
2x=7
x=3.5
p^2-11p+3p-33+p^2+12p+36=2p^2+4p+3
7a^2+14ab+7b^2=7a^2+7b^2
y(y^2-49)=y(y-7)(y+7)
-3(a^2+2ab+b^2)=-3(a+b)
c^2-d^2-c+d=(c-d)(c+d)-(c-d)=(c-d)(c+d-1)
(a-1)(a+1)(a-1)+1)=(a^2-1)*a=(9-1)(-3)=-24
((у-6)-3у)(у-6)+3у)=(-2у-6)(4у-6)
(а-4)(1-4а+4а^2)=(а-4)(1-2а)^2
x-[^2-10x-25=12-5x-30-x^2-6x
-9x-x^2-25=-x^2-11x-18
-9x+11x=-18+25
2x=7
x=3.5
Похожие вопросы
Предмет: Математика,
автор: akbarakmatov68
Предмет: Литература,
автор: enotikdevochka
Предмет: Геометрия,
автор: sofiagoncarova931
Предмет: Математика,
автор: шуро